The relationship between quality of life and functioning for children with cerebral palsy - Shelly, A.; Davis, E.; Waters, E.; Mackinnon, A.; Reddihough, D.; Boyd, Roslyn; Reid, S.; Graham, H. (Wiley-Blackwell Publishing Ltd., 2008)
Given that quality of life (QOL) is commonly confused with functioning, the aim of this study was to examine the association between functioning and QOL domains for children with cerebral palsy (CP). Two hundred and five parents of children aged 4 to 12 years with CP and 53 children aged 9 to 12 years with CP, completed the Cerebral Palsy Quality of Life Questionnaire for Children. Children were distributed reasonably evenly between sex (male, 54.6%) and Gross Motor Function Classification System levels (I 17.8%, II 28.3%, III 14.1%, IV 11.2%, and V 27.3%). For parent proxy-report, all domains of QOL were significantly associated with functioning level except access to services. For child self-report, feelings about functioning, participation and physical health, and pain and feelings about disability, were significantly associated with functioning level. Physical type domains of QOL accounted for more of the variance in functioning than psychosocial type domains. Children with CP have the potential to report a high psychosocial QOL score even if they have poor functioning. © 2008 Blackwell Publishing Ltd.